Indirect signal amplification strategy with a universal probe-based lateral flow immunoassay for the rapid quantitative detection of fumonisin B1. Issue 7 (1st February 2022) - Zha, Chuanyun; An, Xingshuang; Zhang, Jiali; Wei, Lin; Zhang, Qi; Yang, Qingqing; Li, Falan; Sun, Xia; Guo, Yemin
Abstract : The universal probes could combine with any mouse monoclonal antibody, providing bio-material for the simultaneous detection of multiple toxins. The established lateral flow immunoassay with indirect signal amplification was suitable for rapid detection of FB1. Abstract : Fumonisin B1 (FB1) is a serious threat to the health of humans and animals. Herein, a lateral flow immunoassay based on universal detection probes (goat anti-mouse IgG@Eu) that could combine with any mouse monoclonal antibody was applied to detect FB1 in corn and feed. Compared with that based on direct monoclonal antibody labeling, this assay maintained bioactivity and saved consumption of monoclonal antibodies with the indirect signal amplification effect. The results indicated that this assay had higher sensitivity with a limit of detection (LOD) of 0.025 and 0.097 ng mL −1 (0.50 and 1.94 ng g −1 based on sample weight) in corn and feed, respectively. The detection range was about 1–50 ng mL −1 (20–1000 ng g −1 based on sample weight). In addition, the evaluation proved that it had good specificity, accuracy, precision, and applicability, and thus was suitable for the rapid and low-cost detection of fumonisin B1.